Bond market integration in the Common Monetary Area (CMA) - Ramoriting, RetÅ¡elisitsoe Silvia (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
The study reviews the phenomenon of financial integration. During the late 1980s and 1990s, financial market integration around the world increased due to globalisation of investments and the need for higher returns and international risk diversification. The increase was accompanied by a significant increase in private capital flows into developing countries from developed countries. The main goal of the study is to examine bond market integration in the common monetary area The study therefore investigates the co-movement of government bond returns within the CMA using data from Eswatini, Namibia, and South Africa. The study attempts to find the short-run and long-run relationship of these government bond returns using the ARDL cointegration technique. The study uses daily data of 10-year government bond yields spanning from August 2014 to September 2019. The empirical results reveal that there exists a short-run and long-run relationship between South Africa and Eswatini. Between South Africa and Namibia, there only exist a short-run relationship. Just like the previously mentioned studies, the short-run relationship is a result of policy convergence. The lack of long-run relationship between South and Namibia was due to poor institutional developments and limited investment opportunities. In this case, policy measures (or reforms) and a review of the union are necessary to increase integration of these bond markets.
Keywords: Globalization; Globalization -- Economic aspects; Bond market; Rand area; Africa, Southern -- Economic integration; Autoregressive distributed lag (ARDL) model